2008
DOI: 10.1002/jbm.a.31988
|View full text |Cite
|
Sign up to set email alerts
|

Nasal chondrocytes and fibrin sealant for cartilage tissue engineering

Abstract: Hybrid constructs associating a biodegradable matrix and autologous chondrocytes hold promise for the treatment of articular cartilage defects. In this context, our objective was to investigate the potential use of nasal chondrocytes associated with a fibrin sealant for the treatment of articular cartilage defects. The phenotype of primary nasal chondrocytes (NC) from human (HNC) and rabbit (RNC) origin were characterized by RT-PCR. The ability of constructs associating fibrin sealant and NC to form a cartilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…In a more recent study, a construct composed of autologous nasal chondrocytes and fibrin were implanted in the subcutaneous pocket of a nude mouse. 20 These authors reported the formation of compact cartilaginous tissue following implantation. In our study, we selected a solid form of scaffold to maintain the preoperatively planned shape, applying surgical procedures to implant the construct precisely into the desired location for augmentation.…”
Section: Discussionmentioning
confidence: 97%
“…In a more recent study, a construct composed of autologous nasal chondrocytes and fibrin were implanted in the subcutaneous pocket of a nude mouse. 20 These authors reported the formation of compact cartilaginous tissue following implantation. In our study, we selected a solid form of scaffold to maintain the preoperatively planned shape, applying surgical procedures to implant the construct precisely into the desired location for augmentation.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Vinatier et al described the healing of a rabbit articular defect with nasal chondrocytes embedded in a fibrin glue matrix. 15 It is difficult to draw clinical correlations when nasal chondrocytes, for instance, are used to treat joint cartilage defects. Costochondral cartilage grafts are commonly used clinically for ear and nose reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The use of heterotopic chondrocytes as an additional cell source for ACT to improve articular cartilage repair is a promising novel approach (15)(16)(17)(18)(19)(20). To assess possible limitations of this strategy, a detailed characterization of heterotopic chondrocyte biology is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…After prolonged monolayer culture chondrocytes are irreversibly dedifferentiated and no longer suitable for ACT since they do not produce a hyaline-like ECM (9)(10)(11)(12). The use of heterotopic chondrocytes as an additional non-articular cell source might be a promising novel approach in articular cartilage repair and has currently started to attract more and more attention (13)(14)(15)(16)(17)(18)(19)(20)(21). Auricular cartilage contains a considerably higher number of cells and is much more easily accessible as well as being characterized by a lower donor site morbidity, compared with articular cartilage (18).…”
Section: Characterization Of Auricular Chondrocytes and Auricular/artmentioning
confidence: 99%